2022
DOI: 10.1101/2022.09.22.509091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Luminal epithelial cells integrate variable responses to aging into stereotypical changes that underlie breast cancer susceptibility

Abstract: Effects from aging in any single cell are unpredictable, whereas aging phenotypes at the organ and tissue levels tend to appear as stereotypical changes. The mammary epithelium is a bilayer of two major phenotypically and functionally distinct cell lineages, the luminal epithelial and myoepithelial cells. We have shown that mammary epithelia exhibit substantial stereotypical changes with age which merits attention as they are putative breast cancer cells of origin. We hypothesize that effects from aging that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
1
3
0
Order By: Relevance
“…Several DE genes (n=69) in mouse luminal cells were also detected in a recent study of aged human luminal epithelial cells in vitro 67 ( Supplementary Table 3h ). Shared aging patterns between human and mice include the upregulation of: i) Fkbp5 , a regulator of AKT and NFκB pathways, as well as of the androgen–receptor complex, and mostly known for being the target of the drug Rapamycin 68 ; ii) stromal type IV collagen Col4a6 , a protein that is often upregulated in metastatic breast tumors 69 ; iii) Ifi204, an interferon activated protein implicated in DNA repair and STING-mediated type-I interferon production 70 ; iv) Slk , a kinase involved in cell migration downstream of Erbb2 71 ; and downregulation of v) epithelia-specific TF Elf5 , a known marker of luminal aging in humans 72 ; vi) Ntn4 , a regulator of EMT in breast cancer 73 ; v) Tead2 , a TF that belongs to the family of nuclear effectors of the Hippo, TNF, and Wnt pathways 74 .…”
Section: Resultssupporting
confidence: 57%
“…Several DE genes (n=69) in mouse luminal cells were also detected in a recent study of aged human luminal epithelial cells in vitro 67 ( Supplementary Table 3h ). Shared aging patterns between human and mice include the upregulation of: i) Fkbp5 , a regulator of AKT and NFκB pathways, as well as of the androgen–receptor complex, and mostly known for being the target of the drug Rapamycin 68 ; ii) stromal type IV collagen Col4a6 , a protein that is often upregulated in metastatic breast tumors 69 ; iii) Ifi204, an interferon activated protein implicated in DNA repair and STING-mediated type-I interferon production 70 ; iv) Slk , a kinase involved in cell migration downstream of Erbb2 71 ; and downregulation of v) epithelia-specific TF Elf5 , a known marker of luminal aging in humans 72 ; vi) Ntn4 , a regulator of EMT in breast cancer 73 ; v) Tead2 , a TF that belongs to the family of nuclear effectors of the Hippo, TNF, and Wnt pathways 74 .…”
Section: Resultssupporting
confidence: 57%
“…Epithelial tissue within the breast shows maturo-developmental plasticity that supports lactational function. It was recently reported that over the course of time during adulthood, the methylome of healthy proliferating breast epithelial tissues increasingly resembles that of breast cancer (Sayaman et al, 2022;Senapati et al, 2022). This is a potential example of a maturo-developmental process displaying AP.…”
Section: Onto-developmental Fidelity Vs Maturo-developmental Plasticity?mentioning
confidence: 93%
“…SATB1 organizes T cell differentiation [43], epidermis development [44], early postnatal cerebral cortical development [45], and embryonic stem cell differentiation [46]. SATB1 differentially expressed in luminal epithelial cells, and the lineage-specific expression is decreased with age [18]. This raises a potential regulatory mechanism by ELF5 in luminal epithelial cells; ELF5 may interact with SATB1 to orchestrate the regulation of its target genes in the maintenance of luminal epithelial cells and differentiation from luminal progenitors.…”
Section: Elf5 In Normal Breast Developmentmentioning
confidence: 99%
“…Aging alters breast tissue architecture, with increased adipose cell proportions [11], basement membrane disruption [13], and epithelial composition shifts [14]. Lineage fidelity loss in luminal epithelial cells is a hallmark of aging [14][15][16][17], marked by reduced luminal epithelial cell-specific transcriptomes and methylomes, and the gain of myoepithelial celllike features [17,18]. Although loss of fidelity with age is observed in both lineages, it is most pronounced in luminal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%